Video over wi-fi network' system - Zhao, Yi Fan. (2009)
The objective of this project is to construct a prototype for a ‘video over Wi-Fi network’ system. As modern Smartphone have experienced rapid advances in their hardware capabilities, the multimedia communication with such device is becoming more and more popular. With the support of Wi-Fi network, live video streaming is made possible on the Smartphone. The project is an extension of the existing ‘Enhanced SMS and MMS system over Wi-Fi networks’ project, which had implemented Store-and-Forward video streaming. This project will enhance the current system to support real-time video streaming over Wi-Fi network. The streaming server is designed for desktop PC running Windows XP or Windows Vista platform. The server allows capturing video data with a webcam and stream the data to a client. The client is designed for Smartphone running Windows Mobile 5 or Windows Mobile 6 Operating System. The client allows user to connect to a stream server and display the remote video stream lively. The server and client are connected wirelessly either via Ad-hoc network or Intranet. Finally, this project researches on the possibility of migrating the streaming server from desktop PC to Smartphone. The system structure has been designed and implementation suggestions are given. As a result, future work on Smartphone to Smartphone video transmission can be carried on from this point.